2018
DOI: 10.31729/jnma.3467
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Vs Vaginal Delivery : An Institutional Experience

Abstract: Introduction: According to the WHO, 15% of deliveries have precise indication for cesarean section where it is mandatory for the preservation of maternal and/or fetal health. Increasing rates of Lower Segment Caesarean Sections puts foreword various question that, whether a LSCS need to be reflected as a normal delivery in this twenty first century. There are conflicting reports regarding the safety of caesarean sections. While a significant number of cesarean delivery are performed for obstetrical indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
1
19
2
8
Order By: Relevance
“…7 Sharma and Dhakal from Nepal demonstrated similar pattern as well. 8 Furthermore, we observed that deliveries who had a spontaneous onset of labor had the least blood loss. Among the various indications of labor induction, we observed women with oligohydramnios and postdatism to have the maximum blood loss.…”
Section: Discussionmentioning
confidence: 83%
“…7 Sharma and Dhakal from Nepal demonstrated similar pattern as well. 8 Furthermore, we observed that deliveries who had a spontaneous onset of labor had the least blood loss. Among the various indications of labor induction, we observed women with oligohydramnios and postdatism to have the maximum blood loss.…”
Section: Discussionmentioning
confidence: 83%
“…Cesarean sections and routine urinary catheter insertions are particular risk factors for local infections. Therefore, many obstetrics clinics administer antibiotic prophylaxis before cesarean section (4) However, vaginal delivery without risk factors has a lower risk of infection, and routine prophylaxis is not recommended in the current guidelines (5). Our patient presented with a serious infection that developed after vaginal delivery.…”
Section: Discussionmentioning
confidence: 96%
“…De acordo com Sharma et al (2018), em um relato de caso, foi relatado um caso raro de filariose bancroftiana em uma mulher de 32 anos apresentando um pequeno inchaço subcutâneo na face lateral do braço. Foi realizada citologia aspirativa por agulha fina (FNAC).…”
Section: Relato De Casounclassified